Iodine-125 brachytherapy treatment for newly diagnosed brain metastasis in non-small cell lung cancer: A biocentric analysis - Yang, Lili; Wang, Congxiao; Zhang, Wei; Liu, Shifeng; Xuan, Tiantian; Jiang, Han; Hu, Xiaokun; Hu, Man; Li, Huanting (Frontiers in Oncology, 2022)
Purpose The aim of the present study is to evaluate the safety and efficacy of iodine-125 brachytherapy for newly diagnosed brain metastasis in patients with non-small cell lung cancer (NSCLC). Materials and methods The study included 158 NSCLC patients diagnosed with brain metastasis from December 2003 to August 2017. Ninety-nine patients underwent external beam radiotherapy (EBRT group), and 59 patients received iodine-125 brachytherapy (125I group). In addition, the 6- and 12-month progression-free survival (PFS) rates and the 12- and 24-month overall survival (OS) rates were compared between the EBRT group and the 125I group. Median OS and PFS were analyzed using the Kaplan−Meier method with a log-rank test. Results The 6-month PFS rate was significantly higher in the 125I group (p = 0.002) than in the EBRT group, while no differences were found in the 12-month PFS rate (p = 0.184). Additionally, the 12- (p = 0.839) and 24-month (p = 0.284) OS rates were not significantly different between the two groups. No significant differences in median OS (p = 0.525) or PFS (p = 0.425) were found between the two groups. Conclusions Iodine-125 brachytherapy is an alternative therapy for patients unable to undergo surgical resection.